Late-Holocene climatic record from a glacial lake in Ladakh range, Trans-Himalaya, India. (July 2020) - Phartiyal, Binita; Singh, Randheer; Joshi, Priyanka; Nag, Debarati
A multi-proxy study using mineral magnetism, sediment texture, total organic content, palynofacies and diatoms was conducted in one of the highest proglacial lake situated at North Pulu (5098 m a.s.l.) of Ladakh sector of NW Himalaya – a high-altitude cold arid desert. This study presents climatic variations that occurred between 5412 and 419 cal. yr BP ( 14 C AMS chronology). Directly recharged by meltwater from Khardung glacier, this proglacial lake provides a complete record of past climatic variability due to continuous sedimentation and this attribute makes it an exceptionally important geochronological archive for climatic studies. This first high-resolution palaeolimnology record from Karakoram Himalayas shows intermittent warm and cold periods in which the cold events are short but sudden events recorded at 5700, 4600, 4400, 4200, 3800, 3500, 3000, 1800–1700, 1200, 910, 840 and 770–710 cal. yr BP. Between 5412 and 4840 cal. yr BP, an oxic lake condition existed with freeze–thaw action, prominent weathering, more sediment generation and less organic productivity. The following period till 4410 cal. yr BP was cold and dry, a transition phase to the next warmer phase. Between 4410 and 2064 cal. yr BP, climate ameliorated to somewhat moderate warm climate and relatively high lake levels. Glacial melting due to a warm climate resulted in high TOC%, and well-preserved OM indicating reducing conditions in the lake system. From 2064 to 1711 cal. yr BP cold conditions and from 1272 to 1182 cal. yr BP warmer conditions are seen with large appearance in Amphora ovalis indicating increased nutrients input and moderate water levels. This was followed by warmer climatic conditions between 1182 and 958 cal. yr BP. LIA in the region is experienced between 958 and 644 cal. yr BP with anoxic condition. Between 644 and 419 cal. yr BP, climatic condition was again warmer comparatively. However, this warming was not so severe and only had a regional impact.